Weak Localization Enhanced Ultrathin Scattering Media (Advanced Optical Materials 18/2022). Issue 18 (19th September 2022) - Pompe, Ruben C. R.; Meiers, Dominic T.; Pfeiffer, Walter; von Freymann, Georg
Abstract : In article number 2200700, Ruben C. R. Pompe, Dominic T. Meiers, and co‐workers investigate coherent light scattering in ultra‐thin, brilliant white, low refractive index structures, such as the scales of Cyphochilus beetles. It is shown that leakage from resonant, closed scattering pathways is responsible for roughly one quarter of the total scattered light. This weak localization phenomenon increases the time of interaction of light with the thin structure. The reported findings emphasize coherence effects in random scattering media and provide new routes for tailoring efficient scattering optical materials.